RESPONS TINGKAH LAKU IKAN NILA MERAH (Oreochromis niloticus) PADA JARING ARAD (SMALL BOTTOM TRAWL) MODIFIKASI PADA UJI FLUME TANK (SKALA LABORATORIUM) - Simeon, Benaya Meitasari (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Fish have differential response on each part of fishing gear. Small bottom trawl was debated as irresponsible fishing gear always efforted as sustainable fishing gear by modification. Small bottom trawl miniatur with addittional part had modification composed by flapper as non-return device, square mesh selector, and square mesh codend. These modification needs laboratorium test related fish behavior, flapper efectivity, and squaremesh selectivity. Laboratorium test using flume tank usual used for fish behavior observation and fishing gear perform. Method that used was descriptive by case study. Descriptive was facts about fish behavior that obserrved and case study giving detail explaination about background, and spesific characters in this case was small bottom trawl modification. Result of this research were fish response for small bottom modification parts, escape level, and selectivity of square mesh selector. Flapper addition had 95% efectivity. Selectivity of squaremesh selector was shown on 4,7 for F 50 and 4,7 for SF. Selectivity of squaremesh codend was shown on 4,5 for F 50 and 6,4 for SF. Laboratorium test was hoped could giving delination aboout this modification fishing gear on the sea.